1995
DOI: 10.1016/0092-8674(95)90418-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the NF-IL6 gene discloses its essential role in bacteria killing and tumor cytotoxicity by macrophages

Abstract: To investigate the role of NF-IL6 in vivo, we have generated NF-IL6 (-/-) mice by gene targeting. NF-IL6 (-/-) mice were highly susceptible to infection by Listeria monocytogenes. Electron microscopic observation revealed the escape of a larger number of pathogens from the phagosome to the cytoplasm in activated macrophages from NF-IL6 (-/-) mice. Furthermore, the tumor cytotoxicity of macrophages from NF-IL6 (-/-) mice was severely impaired. However, cytokines involved in macrophage activation, such as TNF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
377
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(397 citation statements)
references
References 41 publications
18
377
2
Order By: Relevance
“…Paclitaxel, notably at 5-30 mM, was thus proposed as a TLR4 ligand (Takeda et al, 2003). One of the nuclear targets in the TLR-mediated signaling pathway is NF-IL6, a member of the C/EBP family of transcription factors (Tanaka et al, 1995). NF-IL6 was originally identified as a transcription factor that specifically binds to an IL-1 responsive element in the IL-6 gene promoter (Akira et al, 1990), and was subsequently shown to play an important role in LPS-induced gene expression in macrophages (Gorgoni et al, 2001;Uematsu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel, notably at 5-30 mM, was thus proposed as a TLR4 ligand (Takeda et al, 2003). One of the nuclear targets in the TLR-mediated signaling pathway is NF-IL6, a member of the C/EBP family of transcription factors (Tanaka et al, 1995). NF-IL6 was originally identified as a transcription factor that specifically binds to an IL-1 responsive element in the IL-6 gene promoter (Akira et al, 1990), and was subsequently shown to play an important role in LPS-induced gene expression in macrophages (Gorgoni et al, 2001;Uematsu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As C/EBPb is implicated in the regulation of many different molecular and physiological processes, it is possible that systemic factors are involved in the increased keratinocyte apoptosis as well as the subsequent lack of skin tumorigenesis in carcinogen treated C/EBPb À/À mice. C/EBPb null mice (C/EBPb À/À ) have major defects in their immune system (Screpanti et al, 1995;Tanaka et al, 1995) and C/EBPb is known to be involved in the regulation of numerous cytokines (Poli, 1998) some of which are important in Ras-tumorigenesis (Sparmann and Bar-Sagi, 2005). It is a distinct possibility that the increase in epidermal keratinocyte apoptosis in DMBA-treated C/EBPb À/À mice and subsequent lack of tumor development could be of a systemic nature, perhaps involving alterations in the expression of nonkeratinocyte-derived cytokines.…”
mentioning
confidence: 99%
“…with 2 × 10 5 colony forming units (CFU) of L. monocytogenes (a laboratory strain, 27 kindly provided by Dr Y Dohi) on day 0. This strain was verified by PCR analysis to possess the inlA gene, which is specific for the L. monocytogenes strain.…”
Section: Listeria Infection In Vivomentioning
confidence: 99%